Magnetoelectric coupling and exchange bias effects in multiferroic NdCrO3. (24th March 2016) - Indra, A; Dey, K; Midya, A; Mandal, P; Gutowski, O; Rütt, U; Majumdar, S; Giri, S
Abstract: We report ferroelectricity around  ∼88 K that appears well below T N (∼25 K), unlike other members of R CrO3 series. A synchrotron diffraction study suggests that the occurrence of ferroelectricity in NdCrO3 is coupled to the structural transformation from centrosymmetric Pnma to a non-centrosymmetric Pna21 space group. A strong magnetoelectric coupling is observed in the electric polarization [ P ( T )]. This coupling is significantly influenced by the magnetic field cooling effect, suggesting an exchange bias effect in P ( T ). This exchange bias effect is also revealed by the systematic shift of the magnetic hysteresis loops below T N . The rare occurrence of an exchange bias effect in both the magnetic and electric polarizations associated with a strong magnetoelectric coupling is of fundamental interest, as well as being attractive for technological applications close to liquid nitrogen temperature.